A practical guide to ICF catalogs - Winnard, Keith (IBM redbooks, 2015)
This IBM® Redbooks® publication gives a broad understanding of integrated catalog facility (ICF) catalog environments. It includes suggestions for design, planning, and deployment activities to help you create and maintain a balanced and efficient catalog environment. Four scenarios are provided to illustrate sample implementations of typical activities associated with an organization's requirements.